Prove the following by using Mathematical Induction by using \[n\] in \[N\] :
\[n\left( n+1 \right)\left( n+5 \right)\] is multiple of \[3\] .
Answer
Verified
443.4k+ views
Hint: To prove this statement using mathematical induction, we need to first find the first two steps of the mathematical induction which is necessary to prove the certain statement.
Step One: First prove that the statement or the equation is true for \[n=1\].
Step Two: Assume any variable (in this case) let us presume the variable as \[k\], now prove if the following statement or equation is true for \[n=k\] and if, true then also true for \[n=k+1\].
Complete step-by-step solution:
Now placing the value of \[n=1\] in the equation \[n\left( n+1 \right)\left( n+5 \right)\] to check whether it’s a multiple of three or not.
For \[n=1\], \[n\left( n+1 \right)\left( n+5 \right)\]
\[\Rightarrow 1\left( 1+1 \right)\left( 1+5 \right)\]
\[\Rightarrow 1\times 2\times 6\]
\[\Rightarrow 12\]
Hence, the value \[12\] is a multiple of \[3\] as \[3\times 4\] thereby, the term \[n\left( n+1 \right)\left( n+5 \right)\] is correct for \[n=1\].
After successfully completing the first step let us proceed with the second step of the hint by placing \[n=k\].
For \[n=k\], [\ n \left( n+1 \right)\] \[\left( n+5 \right) \]
\[\Rightarrow k\left( k+1 \right)\left( k+5 \right)\]
\[\Rightarrow k\left( {{k}^{2}}+6k+5 \right)\]
\[\Rightarrow k\left( {{k}^{2}}+6k+5 \right)\]
\[\Rightarrow {{k}^{3}}+6{{k}^{2}}+5k\]
Now assuming that the term \[{{k}^{3}}+6{{k}^{2}}+5k\] is a multiple of \[3\] we equate the result to \[3r\] where \[r\] is the multiple of three which upon multiplication leads to \[{{k}^{3}}+6{{k}^{2}}+5k\] as shown below:
\[3\times r={{k}^{3}}+6{{k}^{2}}+5k\].
Now let us place the value of \[n\] as \[n=k+1\]
For \[n=k+1\], \[n\left( n+1 \right)\left( n+5 \right)\]
\[\Rightarrow k+1\left( \left( k+1 \right)+1 \right)\left( \left( k+1 \right)+5 \right)\]
\[\Rightarrow \left( {{k}^{2}}+3k+2 \right)\left( k+6 \right)\]
\[\Rightarrow {{k}^{3}}+9{{k}^{2}}+20k+12\]
There are already three variables with different degrees let us replace the value of \[{{k}^{3}}\] as \[{{k}^{3}}=3r-6{{k}^{2}}-5k\] from \[3\times r={{k}^{3}}+6{{k}^{2}}+5k\] in the above equation for \[n=k\].
\[\Rightarrow {{k}^{3}}+9{{k}^{2}}+20k+12\]
\[\Rightarrow 3r-6{{k}^{2}}-5k+9{{k}^{2}}+20k+12\]
\[\Rightarrow 3r+3{{k}^{2}}+15k+12\]
\[\Rightarrow 3\left( r+{{k}^{2}}+5k+4 \right)\]
Now as we can see that the above \[3\left( r+{{k}^{2}}+5k+4 \right)\] is a multiple of \[3\] as \[3\times \left( r+{{k}^{2}}+5k+4 \right)\].
Hence, the term \[n\left( n+1 \right)\left( n+5 \right)\] is a multiple of \[3\] for \[n=k+1\] as it is for \[n=k\].
Hence, using mathematical induction we can state that \[n\left( n+1 \right)\left( n+5 \right)\] is a multiple of \[3\] for all the values of \[n\in N\].
Note: Students may go wrong while solving for all the steps required, one must solve for all three values of \[n\] as \[1,k,k+1\] as it is necessary to show that all three cases give the end result as multiple of \[3\]. Now the solution for \[n=k+1\] should be done carefully as it’s a three variable multiplication so first multiply \[k+1\left( \left( k+1 \right)+1 \right)\] of \[k+1\left( \left( k+1 \right)+1 \right)\left( \left( k+1 \right)+5 \right)\] and then multiply the rest and upon multiplication carefully replace the value of \[{{k}^{3}}\] by its above equation when \[n=k\], be careful of the sign when replacing the value of \[{{k}^{3}}\] in \[{{k}^{3}}+9{{k}^{2}}+20k+12\].
Step One: First prove that the statement or the equation is true for \[n=1\].
Step Two: Assume any variable (in this case) let us presume the variable as \[k\], now prove if the following statement or equation is true for \[n=k\] and if, true then also true for \[n=k+1\].
Complete step-by-step solution:
Now placing the value of \[n=1\] in the equation \[n\left( n+1 \right)\left( n+5 \right)\] to check whether it’s a multiple of three or not.
For \[n=1\], \[n\left( n+1 \right)\left( n+5 \right)\]
\[\Rightarrow 1\left( 1+1 \right)\left( 1+5 \right)\]
\[\Rightarrow 1\times 2\times 6\]
\[\Rightarrow 12\]
Hence, the value \[12\] is a multiple of \[3\] as \[3\times 4\] thereby, the term \[n\left( n+1 \right)\left( n+5 \right)\] is correct for \[n=1\].
After successfully completing the first step let us proceed with the second step of the hint by placing \[n=k\].
For \[n=k\], [\ n \left( n+1 \right)\] \[\left( n+5 \right) \]
\[\Rightarrow k\left( k+1 \right)\left( k+5 \right)\]
\[\Rightarrow k\left( {{k}^{2}}+6k+5 \right)\]
\[\Rightarrow k\left( {{k}^{2}}+6k+5 \right)\]
\[\Rightarrow {{k}^{3}}+6{{k}^{2}}+5k\]
Now assuming that the term \[{{k}^{3}}+6{{k}^{2}}+5k\] is a multiple of \[3\] we equate the result to \[3r\] where \[r\] is the multiple of three which upon multiplication leads to \[{{k}^{3}}+6{{k}^{2}}+5k\] as shown below:
\[3\times r={{k}^{3}}+6{{k}^{2}}+5k\].
Now let us place the value of \[n\] as \[n=k+1\]
For \[n=k+1\], \[n\left( n+1 \right)\left( n+5 \right)\]
\[\Rightarrow k+1\left( \left( k+1 \right)+1 \right)\left( \left( k+1 \right)+5 \right)\]
\[\Rightarrow \left( {{k}^{2}}+3k+2 \right)\left( k+6 \right)\]
\[\Rightarrow {{k}^{3}}+9{{k}^{2}}+20k+12\]
There are already three variables with different degrees let us replace the value of \[{{k}^{3}}\] as \[{{k}^{3}}=3r-6{{k}^{2}}-5k\] from \[3\times r={{k}^{3}}+6{{k}^{2}}+5k\] in the above equation for \[n=k\].
\[\Rightarrow {{k}^{3}}+9{{k}^{2}}+20k+12\]
\[\Rightarrow 3r-6{{k}^{2}}-5k+9{{k}^{2}}+20k+12\]
\[\Rightarrow 3r+3{{k}^{2}}+15k+12\]
\[\Rightarrow 3\left( r+{{k}^{2}}+5k+4 \right)\]
Now as we can see that the above \[3\left( r+{{k}^{2}}+5k+4 \right)\] is a multiple of \[3\] as \[3\times \left( r+{{k}^{2}}+5k+4 \right)\].
Hence, the term \[n\left( n+1 \right)\left( n+5 \right)\] is a multiple of \[3\] for \[n=k+1\] as it is for \[n=k\].
Hence, using mathematical induction we can state that \[n\left( n+1 \right)\left( n+5 \right)\] is a multiple of \[3\] for all the values of \[n\in N\].
Note: Students may go wrong while solving for all the steps required, one must solve for all three values of \[n\] as \[1,k,k+1\] as it is necessary to show that all three cases give the end result as multiple of \[3\]. Now the solution for \[n=k+1\] should be done carefully as it’s a three variable multiplication so first multiply \[k+1\left( \left( k+1 \right)+1 \right)\] of \[k+1\left( \left( k+1 \right)+1 \right)\left( \left( k+1 \right)+5 \right)\] and then multiply the rest and upon multiplication carefully replace the value of \[{{k}^{3}}\] by its above equation when \[n=k\], be careful of the sign when replacing the value of \[{{k}^{3}}\] in \[{{k}^{3}}+9{{k}^{2}}+20k+12\].
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE